ETOS KERJA PETANI NENAS DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - LUBIS, DWI NURANI; HIDIR,, ACHMAD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Agricultural development as the realization of government policy has been scattered in various areas with different potentials, because the different potential pertaniuan the implementation of development will be based on the availability of natural resources which is dominant in the area and carrying capacity of the other. A wide range of views as well as working as a farmer saying that it is an independent business that really helps families digelumuri economic life by the wide range of needs.Farmers have the motivation and work ethic, because by cultivating pineapples they can benefit greatly, with pineapple farming farmers can meet the economic needs kelurganya, all farmers who investigators interviewed a farmer cultivating pineapples or pineapple which is the main source of family income farmers. work ethic to the welfare of farmers have an inseparable relationship because farmers who have a strong motivation to success will always memerima criticism and suggestions from the outside, and had prepared carefully about the things that will happen on the field.Kayword; Pineapple, Farmers, Work Ethos